Long-period seismic events at Ubinas volcano (Peru): their implications and potentiality as monitoring tool - Zandomeneghi, D. (2012)
Resumen de artículo presentado en el EGU General Assembly 2012. Disponible en: Geophysical Research Abstracts,v. 14, EGU2012-9359, 2012.